Psychometric properties of the Malay Suicidal Behaviors Questionnaire-Revised (SBQ-R) in Malaysian undergraduates - Ching, Sin Siau; Yee, Kee Tan; Ibrahim, Norhayati; Kõlves, Kairi; Jie, Zhang; Fariduddin, Muhamad Nur; Bee, Seok Chua; Whye, Lian Cheah; Syed Elias, Sharifah Munirah; Mat Ali, Siti Nazilah; In, Serena; Lian, Alex Sheng Lim; et al. (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
The psychometric properties of the Malay Suicidal Behaviors Questionnaire-Revised (SBQ-R) need to be tested as it is increasingly utilized, and there is a lack of a brief, validated scale to examine suicidal behaviors in Malaysia. A total of 713 and 715 undergraduates answered the English and Malay SBQ-R, respectively. Exploratory factor analysis derived a one-factor solution, with a total explained variance of 58.0% accounted for by the four items. Confirmatory factor analyses supported the one-factor model for the Malay SBQ-R, with acceptable fit indices (χ2/df = 0.451, comparative and Tucker–Lewis fit indices = ≥1.000, standardized root mean square residual = 0.014, root mean square error of approximation = 0.000, and 90% CI [0.000, 0.083]). Measurement invariance was achieved when comparing the SBQ-R between the English and Malay versions, indicating that both versions are similar in Malaysian undergraduates. Convergent validity was established through a strong correlation between the Malay SBQ-R and the Malay Yatt Suicide Attitude Scale (r = 0.74; p < 0.001). Good internal consistency was achieved for both the English (α = 0.83; ω = 0.85) and Malay (α = 0.81; ω = 0.84) versions. The Malay SBQ-R has adequate validity and reliability for use in Malaysian undergraduates.